2021
DOI: 10.1159/000513704
|View full text |Cite
|
Sign up to set email alerts
|

MRI Features for Predicting Microvascular Invasion of Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Purpose: Microvascular invasion (MVI) is an important prognostic factor in patients with hepatocellular carcinoma (HCC). However, the reported results of magnetic resonance imaging (MRI) features for predicting MVI of HCC are variable and conflicting. Therefore, this meta-analysis aimed to identify the significant MRI features for MVI of HCC and to determine their diagnostic value. Methods: Original studies reporting the diagnostic performance of MRI for predicting MVI of HCC were identified in MEDLINE and EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
67
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 58 publications
(208 reference statements)
10
67
3
Order By: Relevance
“…SVM is a good classifier, but it may not get good performance when it is directly used for classification, but if it can be combined with a good feature selection algorithm, the classification performance will be greatly improved. showed a similar conclusion that arterial enhancement and arterial peritumoral enhancement were significant predictors for MVI of HCC (50). However, in this study, the results of meta-regression showed no significant difference in the AP or PVP.…”
Section: The Value Of Artificial Intelligence Algorithms For Microvas...supporting
confidence: 69%
See 1 more Smart Citation
“…SVM is a good classifier, but it may not get good performance when it is directly used for classification, but if it can be combined with a good feature selection algorithm, the classification performance will be greatly improved. showed a similar conclusion that arterial enhancement and arterial peritumoral enhancement were significant predictors for MVI of HCC (50). However, in this study, the results of meta-regression showed no significant difference in the AP or PVP.…”
Section: The Value Of Artificial Intelligence Algorithms For Microvas...supporting
confidence: 69%
“…A meta-analysis of MRI features for predicting MVI of HCC performed by Hong et al. showed a similar conclusion that arterial enhancement and arterial peritumoral enhancement were significant predictors for MVI of HCC ( 50 ). However, in this study, the results of meta-regression showed no significant difference in the AP or PVP.…”
Section: Discussionmentioning
confidence: 83%
“…Microvascular invasion (MVI) has been recognized as an independent predictor for early recurrence and poor prognosis after liver resection or transplantation in hepatocellular carcinoma (HCC) [ 1 , 2 ]. Its reported incidence ranges from 15% to 57% according to different diagnostic criteria and study population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical imaging has evolved from a primarily diagnostic tool to an essential role in clinical decision making. Clinically, radiologists use pattern recognition after establishing links between radiological features at CT or MRI images and MVI [ 4 , 5 ], such as arterial peritumoral enhancement, non-smooth tumor margins, and rim arterial enhancement [ 2 ]. The Liver Imaging Reporting and Data System (LI-RADS) has recently been developed and has evolved as a comprehensive and standardized diagnostic algorithm for HCC imaging reporting [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large or huge HCC is often found associated with infiltrative pathological characteristics, ie, micro- or macro-vascular invasion, 19 , 29 , 30 which is usually presented as a non-smooth tumor margin or macrovascular invasion at imaging. 24 , 31 In our study, huge HCC had a higher proportion of non-smooth tumor margin or macrovascular invasion than large HCC (85.7% vs 65.7%).…”
Section: Discussionmentioning
confidence: 99%